Konsistensi Implementasi Hak Menguasai Negara Dalam Upaya Mengatasi Dominasi Perekonomian Asing Guna Mewujudkan Kemandirian Ekonomi Nasional - Suparji Suparji (Jurnal Hukum, 2014)
AbstractThe president—Jokowi, has a mandate from the people to make Indonesia to be more equitable and prosperous. In order to fulfill this mandate, he has set nine priority programs known as the concept of Nawa Cipta. This program calls for concrete steps so as not merely a wish list. The most fundamental thing in economics field is how the constitutional mandate that the right to dominate the state can be realized in the management of economic activities, including in dealing with foreign economic domination in IndonesiaKeywords: implementation, the right to dominate the state, foreign economic domination.  AbstrakPresiden Jokowi telah mendapatkan mandat dari rakyat untuk mewujudkan Indonesia yang lebih adil dan sejahtera. Dalam rangka memenuhi mandat tersebut, telah ditetapkan sembilan program prioritas       yang dikenal dengan konsep Nawa Cipta. Program ini tentunya memerlukan langkah-langkah kongkret sehingga tidak sekedar menjadi daftar keinginan. Hal yang paling mendasar dalam bidang ekonomi adalah bagaimana amanat konstitusi yakni hak menguasai negara dapat diwujudkan dalam pengelolaan kegiatan perekonomian, termasuk dalam mengatasi dominasi perekonomian asing di Indonesia.  Kata kunci: implementasi, hak menguasai negara, dominasi perekonomian asing